Assessment of chemotherapy-related educational needs of colorectal cancer patients - TEZCAN, SONGÜL; RABUŞ, ŞULE (My University, 2022)
Aim Aim of our study was to evaluate cancer patients\" knowledge about their chemotherapy regimens in order to assess educational needs of patients. Methods Study was conducted on 58 colorectal carcinoma patients who were treated in an outpatient chemotherapy unit. These patients had received a 2-page information pamphlet about their chemotherapy treatments before the commencement of treatment. During the first interview with patients, pharmacist collected demographic data and evaluated patients\" knowledge about their medications using a standardized questionnaire. Findings Mean age of the patients was 59.6 +/- 1.3 years; 65.5% were male. Majority (77.6%) of patients were graduates of primary school. Sixty-four percent of these had at least one comorbid disease. Median number of chemotherapy courses already received by patients was 4 (1-9). Fifty-nine percent reported that they did not receive any patient education and 43.1% reported that they did not receive any informative document. Twenty-nine percent of patients did not know what actions to take in case of nausea-vomiting; while 53.4% did not know how to react if their body temperature exceeded 38 degrees C and 25.9% had no idea about dietary necessities. About one-third of patients did not pay attention to oral care. Conclusion Our study showed that patients did not understand (or remember) the basic points about their chemotherapy sufficiently, but remembered the adverse effects they experienced occasionally. Pharmacists will have the chance to increase the level of knowledge of the patients receiving chemotherapy by providing patient education and follow-up.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Oncology pharmacist; colorectal cancer; education; chemotherapy; CLINICAL ONCOLOGY PHARMACIST; MEDICATION MANAGEMENT; PHARMACEUTICAL CARE; THERAPIES